Penerapan Prinsip 5C dalam Pemberian Kredit di Lembaga Perkreditan Desa: Studi Kasus Desa Adat Kukuh - Kadek Dego Nyampuh Wijaya Satria Sari; I Nyoman Kusuma Adnyana Mahaputra; Anik Yuesti; Ni Putu Ayu Mirah Mariati; Ni Wayan Rustiarini (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Village Credit Institution (LPD) is a microfinance institution that plays an important role in driving the people's economy in Bali Province. Non-performing loans are one of the biggest challenges LPDs face, including LPD Desa Adat Kukuh. Therefore, the community service activity to solve the LPD problems is credit analysis training using the 5C principle, including character, capacity, capital, collateral, and condition. This activity aims to improve the competence of LPD employee resources, especially related to applying 5C analysis in providing credit. This community service activity was conducted at the LPD of Desa Adat Kukuh, Marga District, Tabanan Regency. The implementation of the activity used interview, training, and evaluation methods. The evaluation of the effectiveness of the community service activity showed an increase in participant competence of 8.73%. This figure indicates that this training benefits LPD Desa Adat Kukuh employees by strengthening the application of the 5C principle in providing credit to debtors at LPD Desa Adat Kukuh.